Ruptured Aneurysm Trials: The Importance of Longer-term Outcomes and Meta-analysis for 1-year Mortality. Issue 3 (September 2015) - Sweeting, M.J.; Ulug, P.; Powell, J.T.; Desgranges, P.; Balm, R.; ,
Abstract : Objective: To assess current knowledge for the management of ruptured abdominal aortic aneurysm (AAA), based on the 1-year outcomes of 3 recent randomised trials. Methods: An individual patient data meta-analysis of three recent randomised trials of endovascular versus open repair, including 817 patients, was conducted according to a pre-specified analysis plan, report all-cause mortality and re-interventions at 1 year after the index event. Results: Mortality across the 3 trials at 1-year was 38.6% for the EVAR or endovascular strategy patient groups and 42.8% for the open repair groups, pooled odds ratio 0.84 (95% CI 0.63–1.11), p = .209. There was no evidence of heterogeneity in the odds ratios between trials. When the patients in the endovascular strategy group of the IMPROVE trial were restricted to those with proven rupture who were anatomically suitable for endovascular repair, the pooled odds ratio reduced slightly to 0.80 (95% CI 0.56–1.16), p = .240. Conclusions: After 1 year there is a consistent but non-significant trend for lower mortality for EVAR or an endovascular strategy. Taken together with the recent gains in health economic outcomes demonstrated at 1 year in the IMPROVE trial, the evidence suggests that endovascular repair should be used more widely for ruptured aneurysms.